Libby amphibole‐induced mesothelial cell autoantibodies bind to surface plasminogen and alter collagen matrix remodeling. Issue 15 (12th August 2016) - Hanson, Robert; Evilia, Caryn; Gilmer, John; Woods, Linda; Black, Brad; Flores, Raja; Pfau, Jean C.
Abstract: Lamellar pleural thickening (LPT) is a fibrotic disease induced by exposure to Libby amphibole (LA) asbestos that causes widespread scarring around the lung, resulting in deterioration of pulmonary function. Investigating the effects of autoantibodies to mesothelial cells (MCAA) present in the study populations has been a major part of the effort to understand the mechanism of pathogenesis. It has been shown in vitro that human mesothelial cells (Met5a) exposed to MCAA increase collagen deposition into the extracellular matrix (ECM). In this study, we sought to further elucidate how MCAA drive increased collagen deposition by identifying the protein targets bound by MCAA on the cellular surface using biotinylation to label and isolate surface proteins. Isolated surface protein fractions were identified as containing MCAA targets using ELISA. The fractions that demonstrated binding by MCAA were then analyzed by tandem mass spectrometry (MS/MS) and MASCOT analysis. The most promising result from the MASCOT analysis, plasminogen (PLG), was tested for MCAA binding using purified human PLG in an ELISA. We report that serum containing MCAA bound at an optical density (OD) 3 times greater than that of controls, and LA‐exposed subjects had a high frequency of positive tests for anti‐PLG autoantibodies. This work implicates the involvement of the plasminogen/plasmin system in the mechanism of excess collagen deposition in Met5a cells exposed to MCAA. Elucidating this mechanism could contribute to the understanding of LPT. Abstract : Serum from patients exposed to Libby amphibole (LA) asbestos contain autoantibodies that induce collagen production by mesothelial cells (Met5A), indicated as absorbance in a cell‐based ELISA for collagen Type 1. Commercial plasminogen blocking antibodies have the same effect of inducing collagen production. Clearing IgG from the patient serum suppresses the collagen‐inducing effect of the mesothelial cell autoantibodies (MCAA).